Linguistica dei corpora e linguistica tedesca: Nuove prospettive descrittive per morfologia e sintassi per lo studio del tedesco come lingua straniera - Flinz, Carolina (Milano University Press, 2024)
Corpus linguistics, German linguistics and the Teaching of German as a foreign language (Deutsch als Fremdsprache – DaF) are strictly connected disciplines (cf. Fandrych/ Tschirner 2007). This notwithstanding their combination for descriptive, applicative and didactic purposes is still not widespread. In university teaching theory and practice, the connections are in fact mainly binary, between corpus linguistics and German linguistics, between German linguistics and DaF and between corpus linguistics and DaF. On the contrary, the present volume aims at bringing out the interconnections among all three disciplines; the use of empirical approaches intended to foster the development of linguistic and crosslinguistic awareness will play a central role. The focus of the volume is on morphology and syntax, two linguistic domains that are traditionally considered central to grammar and that are well suited to be understood and analysed by means of corpus linguistics corpus linguistics. Their analysis may serve as a model for other linguistic levels.